(2x-1)(x+5)=O

Simple and best practice solution for (2x-1)(x+5)=O equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-1)(x+5)=O equation:


Simplifying
(2x + -1)(x + 5) = O

Reorder the terms:
(-1 + 2x)(x + 5) = O

Reorder the terms:
(-1 + 2x)(5 + x) = O

Multiply (-1 + 2x) * (5 + x)
(-1(5 + x) + 2x * (5 + x)) = O
((5 * -1 + x * -1) + 2x * (5 + x)) = O
((-5 + -1x) + 2x * (5 + x)) = O
(-5 + -1x + (5 * 2x + x * 2x)) = O
(-5 + -1x + (10x + 2x2)) = O

Combine like terms: -1x + 10x = 9x
(-5 + 9x + 2x2) = O

Solving
-5 + 9x + 2x2 = O

Solving for variable 'x'.

Reorder the terms:
-5 + -1O + 9x + 2x2 = O + -1O

Combine like terms: O + -1O = 0
-5 + -1O + 9x + 2x2 = 0

The solution to this equation could not be determined.

See similar equations:

| 2m+5=33 | | v-1/5=-1/5v-5/2 | | 2ln(x)=ln(3x+10) | | x/3-x/4 | | 40a+30b=630 | | X^2+y^2-4x+6y+2k-1=0 | | G/12-13=14 | | 3+4x+20-30=90 | | X^2-3x-8=7x-29 | | x-2=x+12 | | 3.2-7y=16y-1.89 | | 3x+20x+60-x-3= | | 3x-20x+60-x+3= | | -18x+63= | | 2744)1/3 | | 3x+5(-4x+12)-(x-3)= | | 9x^2+12+4=6 | | 7(2x-1)+5y-6=3y-2(3y)+3 | | 2/3x9/8 | | (4x)m+(5x+1)+(5x+3)m=102 | | -3b-5b-2b=80 | | -12r+15r=21 | | 10z+2z-13z=45 | | 18a-14a=36 | | -3s+8s-10s=35 | | 6y-8y-y=27 | | 7t-4t=24 | | 6x+2-4x-8x=16x+12+3x | | x^2-6y+2x-3xy=0 | | -5r-2r-s=-16 | | Z^4-8z^2+16=0 | | ln(5-x)+ln(2-x)=ln(28-4x) |

Equations solver categories